Origins of a performance audit and development in the world and in Lithuania - Mackevičius, Jonas; Šalienė, Asta (Buhalterinės apskaitos teorija ir praktika, 2020)
As the need for rational use of resources, environmental protection and social welfare increases, so does the importance of performance auditing. Historical knowledge of its origins and evolution makes it possible to understand what a performance audit is, for whom it is intended and what the purpose of its performance is. The aim of the article - to present the development stages, regulation and peculiarities of performance audit in the theoretical aspect in foreign and Lithuanian literature. Research methods of scientific literature analysis, historical, comparative, information grouping, systematization and generalization were applied to achieve the goal. The article reveals the transformation of performance auditing from social auditing to private equity entities to the current performance auditing, which is regulated and applied in the assessment of the performance of public entities. The article examines the development of performance auditing in four stages: 1940-1950, the first attempts to evaluate performance by social parameters; 2) 1950-1970 develops two approaches distinguishing social and economic parameters; 3) 1970-1990 regulation of the field of performance audit, the first research; 4) 1990-2020 adjusts and approves performance audit standards and guidelines, extensive research. During the relevant period, there were different scientific discussions on performance evaluation and performance auditing. The article reveals the problem of the versatility of performance auditing, which creates preconditions for further research.